Vladimir Jankélévitch : The Time of Forgiveness - Looney, Aaron T. (Book collections on Project MUSE., 2015)
"Discusses the moral and metaphysical philosophy of Vladimir Jankelevitch, his reflections on the conditions for forgiveness, especially in light of the Shoah, and the temporality of forgiveness in its relation to creation, history, and memory"--